Accelerating HIV vaccine development using non-human primate models - Mohammad Arif Rahman; Marjorie Robert-Guroff (Taylor & Francis Group, 2019)
Introduction: The search for a preventative HIV vaccine is ongoing after three decades of research. Contributions of non-human primate (NHP) models to this research are irrefutable, however interpreting data obtained for translation to humans has been problematic. As knowledge concerning NHP models has accumulated, their utility and value in assessing immunogenicity and efficacy of novel vaccines have become apparent. NHP models have become a critical component of vaccine design. Areas covered: Beginning with early vaccine studies, we trace the development and evolution of NHP models concurrent with changes in HIV vaccine concepts and in response to their ability to predict clinical trial efficacy. The value of NHP studies in guiding vaccine design is highlighted along with their importance in opening new areas of investigation and facilitating movement of promising approaches into the clinic. Expert commentary: Due to their close relatedness to humans, NHPs are an excellent choice for immunogenicity studies. The ability of NHP models to predict clinical efficacy has improved with the introduction of low-dose challenge viruses and recognition of confounding variables in study outcomes. Use of NHP models has opened new research areas with outstanding potential for generating vaccine efficacy against HIV and other infectious agents.